TOTAL AND DIFFERENTIAL LEUCOCYTES OF LANDRACE SWINE WERE GIVEN FEED WATER HYACINTH (Eichornia crassipes) FROM LEAD (PB) POLLUTED WATER - Paramita, Komang Suciani; Mahardika, I Gede; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2016)
The aim of this study was to determine the effect of water hyacinth ( Eichornia crassipes ) collected from Lead (Pb) polluted water in feed tota l and differential leukocyte counts of pigs. This study was an experimental study and done used a completely randomized design. The sample that been used was blood from a total of eight Landrace swines, consisted of four groups: pigs were feed without hyacinth (A), pigs were feed with 2,5% hyacinth (B), pigs were feed with 5% hyacinth (C), and pigs were feed with 7,5% hyacinth (D). Blood were then collected from auricularis superficialis vein. The total and differential leukocytes were checked in the Clinical Pathology Laboratory, Faculty of Veterinary Medicine, Udayana University. Total leukocytes count were measured by auto analyzer Scil Vet ABC (ABC Vet 16p) . The blood were also processed for blood smear preparation by Giemsa staining before performing examination by using 100x magnificence under a microscope using straight edge method. Data were then analyzed by one-way ANOVA . The results showed that the administration of water hyacinth ( Eichornia crassipes ) collected from Lead (Pb) polluted water was not influence the to tal and differential leukocyte counts in pigs .
Keywords: babi Landrace; eceng gondok; timbal (pb); total leukosit; diferensial leukosit; Landrace swine, water hyacinth; lead (Pb); total leukocytes; differential leukocytes